Conflict of Law Enforcement by State Institutions over Abuse of Power and Authority: A Case Study of "Former President Director of PT. Pertamina" - Harlina, Indah; Riyadi, Bambang Slamet (International Journal of Criminology and Sociology, 2022)
This study, wants to analyze the very significant differences in the application of legal considerations on the abuse of power and authority by the former President Director of PT. Pertamina, which caused losses to the state based on legal considerations by the Corruption Court Judge and the Jakarta High Court, decided to imprisonment for 8 years and a fine. However, a cassation decision by the Panel of Judges at the Supreme Court of the Republic of Indonesia stated that the defendant was presumed innocent and freed the defendant from the demands of imprisonment and unconditional release. The problem of this research is, Why are there very significant differences in the application of law in the same state institution? The purpose of this study, for Constitutional Law academics can provide a very significant difference study in legal considerations in the Court of Justice in Indonesia. For judges at the Supreme Court of the Republic of Indonesia as an introspection in the legal consideration of abuse of power that results in losses to the state. This research approach method was a qualitative method. Creswell defines a qualitative method as a research method that is based on the perspective of constructivism, in which various meanings are socially and historically constructed with a view to develop a theory or pattern. The researcher analysis was based on legal regulations where conflicts occurred in the law enforcement among the three state institutions acting as the basis of constitutional law, which were; Jakarta Corruption Court; High Court of Appeals for the Special Capital Region of Jakarta; and Supreme Court of the Republic of Indonesia.The results of the research show real evidence, the application of law, abuse of power and authority in state-owned enterprises, which was carried out by the former President Director of PT Pertamina so that the state suffered losses. At the Corruption Crime Court and the Jakarta High Court apply the Corruption Crime Law, but the Supreme Court of the Republic of Indonesia applies business law. In terms of this significant difference, it has resulted in constitutional law academics assessing decisions that do not reflect a sense of justice. The researcher's suggestion is that the panel of judges in a state institution should have no differences in taking legal considerations on abuse of power and authority that harm the state.